Analisis Pengaruh Lingkungan Kerja, Kepuasan Kerja dan Komunikasi Terhadap Kinerja Karyawan Pada PT. Siam-Indo Gypsum Industry - Remy R.T.K Lolong; Asrul; Andi Muhammad Sadli (Mulia Pratama, 2023)
The purpose of this study was to identify the influence of the work environment, job satisfaction and communication on the performance of civil servants, either par tial or simultaneously, to employee performance PT. Siam-Indo Gypsum Industry. This study uses the method of hypothesis testing and the data were analyzed using regression and correlation, analysis is performed using the software Statistical Product and Service Solutions (SPSS) version 26. The population in this study were all employees of PT. Siam-Indo Gypsum Industry amounted to 100 personnel. The sample in this study was determined based on Slovin method amounted to 50 personnel. The results of statistical studies show that the work environment, job satisfaction and communication, either partially or simultaneously significantly affect the performance of employees in PT. Siam-Indo Gypsum Industry. Partial correlations of independent variables on the dependent variable at a strong level. From the observations and data analysis can be summarized as follows: (1) based on the result of the regression analysis, the equation is Y = 6,411 + 0,224 X1 + 0,345 X2 + 0,343 X3 can be seen that the variable work environment, job satisfaction and communication has a positive correlation to the performance of employees of PT.Siam-Indo Gypsum Industry, (2) in accordance with the result of t-test analysis, variable work environment t count < t table means that no effect. On variable job satisfaction and communication t count > t table means this two variable have a significant correlation to the performance of employee, (3) of the F test, it can be concluded that the independent variables correlated to employee performance, (4) of the R test result obtained 65,4% means that the reliability of the dependent variable that can be explained by the independent variables by 65,4% and the remaining 34,6% influenced by other variables.